Synthesis and characterization of photo-responsive azobenzene side-chain liquid crystalline polystyrenes with a mesogenic phase of wide temperature range. (February 2023) - Zhang, Ruixue; Ma, Hongwei; Li, Xuwen; Yang, Jiaxin; Lai, Meng; Zhang, Xueli; Wang, Yu; Li, Yang; Han, Li
Abstract: Polystyrenes (PSs) that provide photochemical stability are commonly used as the chromophore macromolecular carriers. Herein, PS-based alternating copolymers, i.e., alt -P(D- SiH /Ip), alt -P(D- 2SiH /Ip) and alt -P(D- SiH /St), are synthesized through anionically copolymerized Si–H functionalized 1, 1-diphenylethylene (DPE-SiH/2SiH) with isoprene (Ip)/styrene (St). Anionically polymerized (4-vinylphenyl)-dimethyl-silane is used as the uniform hydrosilylated PS, i.e., Uni. -P(St- SiH ). A series of photo-responsive azobenzene side-chain liquid crystalline PSs combine the above PS-based main chains and the mesogenic moiety composed of azobenzene (Azo) and cholesterol (Chol) groups, i.e., Azo-Chol (M), via the hydrosilylation. The polarized optical microscopic (POM) morphologies and thermal properties of Azo-Chol (M) and Azo-Chol-PSs are studied. As desired, they produce the cholesteric phase of wide temperature range due to the PSs and Chol-groups. Moreover, the photo-responsive behavior irradiated under UV-light of different wavelengths are quantitatively evaluated by time-dependent UV–Vis spectroscopy. Azo-Chol-PSs undergo rapid and reversible trans-cis isomerization under the alternating irradiation of UV and visible light. The trans -to- cis isomerization efficiency under 365 nm UV-light is over that under 290–320 nm UV-light, while over 80% of cis -to- trans efficiency can be realized under 400–500 nm Vis-light irradiation This work would provide guidelines for the effective design of photo-responsive anisotropic materials. Graphical abstract: Image 1 Highlights: Vinyl-terminated mesogenic moiety composed of Azo and Chol-groups was synthesized. PS-based main chains and side-chain liquid crystalline PSs were obtained. The well-defined Azo-Chol-PSs with a mesogenic phase of wide temperature range was achieved. The photo-responsive behavior of Azo-Chol-PSs irradiated under UV-light with were studied.